Familial Reversible Cerebral Vasoconstriction Syndrome: Insights From Two Families - Pacôme Constant dit Beaufils; Benoît Guillon; Hugues Chabriat; Solène de Gaalon (Case Reports in Neurological Medicine)
Reversible cerebral vasoconstriction syndrome (RCVS) is a rare condition whose exact underlying mechanisms remain undetermined. Herein, we report two exceptional family cases suggesting that a potential genetic factor might be involved in this condition. A mother and her daughter presented with recurrent thunderclap headaches and reversible vasoconstriction of the right middle cerebral artery in the first family. Clinical features suggestive of RCVS associated with a discrete subdural hemorrhage was observed in a mother and her daughter in a second family. These familial observations of RCVS suggest the existence of a genetic factor promoting the emergence of this condition.